Discrete-Event Control and Predictive Optimization of Fuel Tankers and Pumps Allocation - Adrian Ramanda; Nur Faizatus Sa'idah; Rully Tri Cahyono (Program Studi Teknik Industri, Fakultas Teknologi Industri, Institut Teknologi Bandung, 2023)
This paper deals with a dynamic scheduling model of a general fuel tankers and pumps operations. The models are dynamics because the ships’ arrival time is allowed to vary. The goal of the study is to determine the optimal berth allocation/scheduling and the policy recommendations, which minimize ships’ total waiting time, berth occupancy ratio, and ships’ charter cost. Discrete-event Systems (DES) modeling is chosen due to aperiodicity in ships’ arrival time and asynchrony operations’ time among different berthing positions. Two DES models are developed, i.e.: (1) multiple cost allocation problem (MBAP) for the supply jetty and (2) simple berth allocation problem (SBAP) for the consignment jetty. Furthermore, we use model predictive control (MPC) to optimize the DES model, and we also provide mathematical analysis of the proposed algorithm. Numerical examples examining two cases (tidal and non-tidal) in each of the two models are presented to illustrate the optimal solution. The problem encountered is that current berth allocation is not working efficiently, as indicated by the average waiting time for ships at the supply jetties (jetties 1 and 2) which is above the standard (14 hours), while the consignment jetty (jetty 3) is well below standard.